Correlation of glutamate levels in the anterior cingulate cortex with self-reported impulsivity in patients with borderline personality disorder and healthy controls - Hoerst, Mareen; Weber-Fahr, Wolfgang; Tunç-Skarka, Nuran; Ruf, Matthias; Bohus, Martin; Schmahl, Christian; Ende, Gabriele (Archives of general psychiatry, 2010)
Borderline personality disorder (BPD) is a severe, often debilitating mental disorder that affects approximately 2% of individuals in the community and up to 20% of psychiatric inpatient samples. In general, BPD typical behavior includes impulsivity, affective instability, and difficulty in controlling anger. These behaviors are manifestations of a core syndrome of BPD: pervasive malfunction of the affect regulation system. Self-reported impulsivity seems to be a stable trait over time and highly predictive of BPD psychopathology over long-term follow-up.Regarding the neural underpinnings of affective dysregulation in BPD, dysfunction in the limbic and prefrontal regions has been reported in BPD. This frontolimbic network primarily consists of the anterior cingulate cortex (ACC), orbitofrontal and dorsolateral prefrontal cortex, hippocampus, and amygdala. The ACC is involved in both cognitive and affective functions, which can be associated with BPD-related symptoms, including impulsivity, cognitive distortions, and affective instability.